Corruption and anticorruption measures in Romania - Precupețu, Iuliana (Calitatea Vieții, 2007)
Various studies place Romania in the category of countries characterised by a high level of corruption. The article describes the position held by the country under scrutiny with regard to different types of corruption among other countries in Europe, while also trying to portray several accounts of the phenomenon. Finally, anticorruption measures are reviewed, setting, thus, a general framework of the corruption phenomenon in Romania.